Utilizing Grammarly in an Academic Writing Process: Higher-Education Students’ Perceived Views - Faisal Faisal; Primita Arif Carabella (Journal of English Language Teaching and Linguistics, 2023)
This small-scale study looks into the English-Language-Education-Program (ELE) students’ perceived views on using Grammarly as an automatic grammar checker in an academic writing process. It adopted a questionnaire instrument Novianti (2020) employed in her study. The interval scale average of 73.3% indicated that most students positively perceived using Grammarly in the academic writing process. They deemed that this application could help them revise their errors in the academic writing process, improve their academic writing, and boost their confidence in academic writing. On the other hand, some students negatively perceived using Grammarly in their academic writing process due to the nature of feedback this application offers. Furthermore, this study considered that factors that might have affected both views were associated with Grammarly’s handy and practical use and non-contextual and irrelevant feedback. This study is a small-scale one, primarily investigating students’ perceptions of the use of Grammarly application in an academic writing process. Future research can expand such dimensions as students’ attitudes in using this application or the impacts of Grammarly on students’ writing anxiety. Moreover, it can investigate students’ perceptions of the use of the application in an academic writing process by employing different instruments and indicators of perception.